Application For Marriage Dispensation For Underage Pregnant Women Post The Application Of Law Number 16 Of 2019 Concerning Amendment To Law Number 1 Of 1974 Concerning Marriage - Djunastuti, Erni; Alhadiansyah, Alhadiansyah; Susila, Sugeng; Marnita, Marnita; Tahir, Muhammad (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
In essence, everything in this world God created in pairs, as well as humans. Nowadays, teenagers are very easily influenced by their friends and fall into promiscuity, in which they commit acts that are prohibited by religion and violate religious norms. This causes a lot of negative things for them, one of which is pregnancy outside of marriage, so that early marriage occurs. Early marriages that have not reached the age of 19 years can request dispensation from marriage to the Office of Religious Affairs and the Office of the Religious Courts. Marriage dispensation is a relief given by the court to prospective husbands or wives who wish to carry out a marriage, where the age of one or both of the prospective brides has not yet reached the age limit stipulated in Law Number 16 of 2019 concerning Amendments to the Law. Law Number 1 of 1974 Concerning Marriage. The problem in this study is "Application for Dispensation for Marriage for Underage Pregnant Women After the Enactment of Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage". The research method used by the author is this type of research is using Empirical or Sociological legal research, meaning that the research is carried out by the author by going directly to the research location to get results by using a result collection tool in the form of interviews. The results of this study indicate that the Religious Affairs Office of North Pontianak Subdistrict and Judges at the Pontianak Religious Court gave an emergency dispensation for being pregnant out of wedlock, namely because the judge had heard information from the Petitioner, Children, Prospective Husband/Wife, and Parents/Guardians of the Prospective Husband/ Wife and have considered the statements of the parties concerned, and have examined the terms and evidence submitted by the applicant. As well as the legal consequences of granting dispensation from marriage to minors due to pregnancy out of wedlock, namely by being granted dispensation from marriage, minors can carry out marriages, where previously minors could not carry out marriages that were registered by law, then they could because have received permission for dispensation of marriage, then the status and position of the child is clear, and the position of husband and wife is present.